A retrospective study of alendronate for the treatment of ankylosing spondylitis. Issue 20 (May 2018) - Li, Gang; Lv, Chang-an; Tian, Li; Jin, Lian-jin; Zhao, Wei
Abstract : Abstract: This retrospective study assessed the effect of alendronate for treating patients with ankylosing spondylitis (AS). Eighty-six patients with AS were included in this retrospective study, and were divided into 2 groups. Forty-six patients in the intervention group received alendronate plus vitamin D (400 mg/day) and calcium (500 mg/day), while 40 patients in the control group received vitamin D and calcium only, the same dose as the intervention group. The primary outcome included bone densitometry. The secondary outcomes consisted of quality of life, measured by Ankylosing Spondylitis Quality of Life (ASQoL) questionnaire, disease activity, measured by Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), and functional status, measured by Bath Ankylosing Spondylitis Functional Index (BASFI), as well as the adverse events (AEs). At the end of 6-month treatment, patients in the intervention group were not superior to the patients in the control group in bone densitometry (hip, P = .47; lumbar, P = .53), quality of life ( P = .32), disease activity ( P = .39), and functional status ( P = .41). Moreover, no significant differences in AEs were found between 2 groups. The results of the present study showed that alendronate can neither be used to treat bone loss, nor to enhance the quality of life, disease activity, and functional status.